Analysis of a series of Italian APECED patients with autoimmune hepatitis and gastro-enteropathies - Paldino, Giorgia; Faienza, Maria Felicia; Cappa, Marco; Pietrobattista, Andrea; Capalbo, Donatella; Valenzise, Mariella; Lampasona, Vito; Cudini, Annamaria; Carbone, Elena; Pagliarosi, Olivia; Maggiore, Giuseppe; Salerno, Mariacarolina; et al. (Frontiers in Immunology, 2023)
Introduction: Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome is a rare monogenic disease determined by biallelic mutations in AIRE gene, which encodes a transcription factor essential for central immune tolerance. Classic diagnosis is determined by the presence of two of the main APECED clinical diseases: chronic mucocutaneous candidiasis, chronic hypoparathyroidism and Addison’s disease. Non-endocrine autoimmunity, involving liver, intestine, eyes and kidneys, is generally reported in a minority of European patients while American APECED patients have a higher tendency of developing organ-specific non-endocrine manifestations early in the life. This observation led to revise the diagnostic criteria to permit earlier diagnosis based on the appearance of one classic triad symptom or one non-classical manifestation at young age in presence of IFNωAbs or AIRE mutations (Ferre- Lionakis criteria). Patients and Methods: We analysed the clinical, genetic and autoantibody (Abs) profile in a series of 14 pediatric Italian APECED patients with gastrointestinal manifestations (seven males, seven females). Ten patients presented hepatitis (APAH) while seven were affected by constipation, diarrhea and malabsorption. Four patients had developed APAH before classic triad symptoms. Results: Based on the age of appearance of non-endocrine manifestations including APAH and gastro-enteropathy, the Ferre-Lionakis criteria would have allowed an expedited diagnosis in 11/14 patients. Abs to tryptophan hydroxylase (TPHAb) and hepatic aromatic L-aminoacid decarboxylase (AADC) were significantly associated in APECED patients of the present series. Abs to cP4501A2 were detectable in the serum of 4/8 patients with APAH and Abs to cP4502A6 in 3/8 patients. AADC Abs tested positive in 5/7 patients which are indicative of gastrointestinal dysfunction in APECED and TPHAb in 5/7 patients with gastrointestinal dysfunction. IFNAb were significantly associated with the syndrome. Conclusion: Although Ferre-Lionakis expanded criteria applied to the American cohorts of APECED patients would require validation in independent large cohorts of European patients, the results of this study emphasize the importance to evaluate the presence and the age of appearance of APAH and autoimmune enteropathy even in European cohorts for an earlier APECED diagnosis. As an earlier APECED diagnosis would also allow prevention of episodes of life-threatening hypocalcemic seizures and adrenal crisis, which are the main manifestations of undiagnosed APECED.